Riesgos ergonómicos y prácticas de autocuidado del personal de enfermería del servicio de centro quirúrgico. Hospital III Essalud, Iquitos 2022 - Caja Flores, Lilibeth Yuvitza (2023)
The objective of the research was to know the relationship between self-care practices and ergonomic risks in nursing professionals who work in the surgical center of the EsSalud III hospital in Iquitos 2022. In the methodology, the type of research was quantitative, descriptive, correlational, non-experimental, prospective, transversal design. The sample was made up of 36 people (20 nursing professionals and 16 nursing technicians). The main results were: 77.8% of nursing staff are exposed to low-level ergonomic risks and 22.2% to high-level ones; 97.2% rated inadequate and 2.8% adequate self-care practices; obtaining a strong significant negative relationship between ergonomic risks and self-care practices according to the Spearman Rho correlation coefficient statistical test (p=0.000; <0.05), accepting the proposed hypothesis. It is concluded that the majority of nursing staff is exposed to low ergonomic risks, showing inadequate self-care practices.